Paediatric extra-axial myxopapillary ependymoma: what to expect? Case report and literature review - Lo Piccolo, Roberto; Cianci, Maria Chiara; Sardi, Iacopo; Di Nicola, Marco; Buccoliero, Anna M.; Caporalini, Chiara; Morabito, Antonino (Frontiers in Oncology, 2025)
Extra-axial ependymomas are rare tumours, and myxopapillary ependymoma (MPE) is the most common subtype in children, often misdiagnosed as other sacral lesions. MPEs are considered low-grade tumours, but relapse with distant metastasis is frequent. Therefore, therefore a proper diagnosis and subsequent follow-up are warranted. The current report presents a case of extra-axial MPE in a paediatric patient who presented with an indolent sacral mass and underwent surgical resection, along with a review of the literature. The aim was to highlight the importance of diagnostic suspicion in differential diagnosis of sacral soft-tissue masses